2011
DOI: 10.1126/science.1210280
|View full text |Cite
|
Sign up to set email alerts
|

Uninformed Individuals Promote Democratic Consensus in Animal Groups

Abstract: Conflicting interests among group members are common when making collective decisions, yet failure to achieve consensus can be costly. Under these circumstances individuals may be susceptible to manipulation by a strongly opinionated, or extremist, minority. It has previously been argued, for humans and animals, that social groups containing individuals who are uninformed, or exhibit weak preferences, are particularly vulnerable to such manipulative agents. Here, we use theory and experiment to demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
379
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(404 citation statements)
references
References 21 publications
20
379
1
4
Order By: Relevance
“…Movement leaders [15,16], knowledgeable tutors [17,18], disease super-spreaders [19,20], hyperaggressive males [21] and social arbitrators [22,23] represent just some of the ways in which one or a few individuals can influence entire societies. Interestingly, evidence from dozens of field studies indicates that the effects of keystone individuals on group success can range from beneficial to disastrous, depending on numerous circumstances [14].…”
Section: Introductionmentioning
confidence: 99%
“…Movement leaders [15,16], knowledgeable tutors [17,18], disease super-spreaders [19,20], hyperaggressive males [21] and social arbitrators [22,23] represent just some of the ways in which one or a few individuals can influence entire societies. Interestingly, evidence from dozens of field studies indicates that the effects of keystone individuals on group success can range from beneficial to disastrous, depending on numerous circumstances [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, using groups of ten birds, no such effect was detected, which may indicate that influencing flockmates' movements is easier in smaller groups. Also, theoretical work by Couzin et al (2011) showed that the presence of uninformed individuals can inhibit decisions made by a knowledgeable minority and enable the numerical majority to control movements. Investigating the potential link between group size and group dynamics -both empirically and theoretically -is a promising avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Group-level properties, such as the collective movements of animal groups, emerge when individuals respond to the location and movements of their near neighbours [2][3][4]. This responsiveness to the behaviour of neighbours allows consensus to be reached over the timing and direction of group movements [5,6]. This in turn allows groups to maintain their coherence and enables group members to realize the benefits of group living [7].…”
Section: Introductionmentioning
confidence: 99%